Rehabilitation Diagnosis Based on the International Functioning Classification (ICF) in Patients under Lower Limb Joint Endoprosthetics - Tatiana V. Builova; Rezeda A. Bodrova; Roza V. Petrova (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
To date, the introduction of the International Classification of Functioning, Disability and Health (ICF) into the practical work of rehabilitationinstitutions and units of different levels and different profiles is a key moment in the organization of the rehabilitation processin accordance with a new legislative framework and a new model of the medical rehabilitation system being created in Russia. Namely,the ICF is the basis for the rehabilitation diagnosis formulation as well as rehabilitation goals and the development of the rehabilitationstrategy for each individual patient, and the practical ICF use presents the greatest difficulties for members of the multidisciplinaryrehabilitation team (MDRT), since it requires to restructure their thinking stereotypes and behavior « from dysfunction - to limitation ofactivity"», «from correction of disorders to restoration of activity». In this regard, the ICF usage issues in the process of rehabilitation ofpatients who underwent arthroplasty of large joints, presented in this article, are very relevant.Aim. To describe the most frequent ICF domains used in the formulation of a rehabilitation diagnosis in patients who have undergonethe lower limb joints replacement.Conclusion. Identification of key problems based on ICF in patients undergoing total knee and hip arthroplasty allows a more focusedand specialized approach to the rehabilitation process for this category of patients, correct formulation of rehabilitation goals and drawingup a plan of rehabilitation measures. In patients who have yet to undergo joint replacement, the use of classification allows to clarifythe indications for surgical intervention.